(3JgGaJ GdadGSaIs - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s
(3ChdgG (B:s
(3Ghd GdehLhO efg ai Cf GdTF GdhGMO dGjchf ehLhO s
(3BNQgG (B:s
(3hCfeG ZQVfG ai Pdc JHjf Cf GdYbd djS eSJbdkG GdCehQ GdEdgjI dMbGFbgG hGfXGQg djSJ eeG jhKb HgG hdfNJe GdcJGH MGeOjf Gddg s
(3GdeNWhW YHGQI Yf eLQO bWYI ef GdeNWhW GdCUdi cJHJ Hbde eged GdfbW Ydi gGeTgG fbhd ddEeGe GdQGRi ai GdeYGO GdQhMGfi hGdLSeGfis
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
Keywords: (3GdadSaI hGdefWbs